The Role of Character Education in Improving Student Discipline at Gadingmangu 1 Elementary School - Nurmala; Wiputra Cendana (Journal of Creative Power and Ambition (JCPA), 2026)
Character education is an important component in the educational process that aims to shape the personality of students as a whole, including in terms of discipline which is the foundation of successful learning. This study aims to describe the role of character education in improving student discipline at SDN Gadingmangu 1. The method used is a qualitative case study with data collection techniques in the form of observation, in-depth interviews, and documentation studies. The research subjects consisted of the principal, class teachers, and students of grades III, IV, and V as well as two parents as supporting data sources. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of character education at SDN Gadingmangu 1 is carried out through daily routine habits, teacher role models, the application of school rules, and the integration of disciplinary values ​​in learning activities.It has been proven that routine activities such as morning ceremonies, class responsibilities (class duty), and awards for high-achieving studentsable to form disciplined habits graduallyPunctual attendance, adherence to school policies, and accountability in completing assignments all indicate improved student discipline. This study concludes that character education, if implemented consistently and systematically and supported by various parties, will significantly contribute to the development of disciplined character in elementary school students.